Comparative transcriptional analysis provides insights of possible molecular mechanisms of wing polyphenism induced by postnatal crowding in Aphis gossypii - Jichao JI; Shuai ZHANG; Junyu LUO; Li WANG; Xiangzhen ZHU; Kaixin ZHANG; Lijuan ZHANG; Jinjie CUI (Journal of Cotton Research, 2019)
Abstract Background Aphis gossypii is a worldwide sap-sucking pest with a variety of hosts and a vector of more than 50 plant viruses. The strategy of wing polyphenism, mostly resulting from population density increasing, contributes to the evolutionary success of this pest. However, the related molecular basis remains unclear. Here, we identified the effects of postnatal crowding on wing morph determination in cotton aphid, and examined the transcriptomic differences between wingless and wing morphs. Results Effect of postnatal crowding on wing determination in A. gossypii was evaluated firstly. Under the density of 5 nymphs·cm− 2, no wing aphids appeared. Proportion of wing morphs rised with the increase of density in a certain extent, and peaked to 56.1% at the density of 20 nymphs·cm− 2, and reduced afterwards. Then, transcriptomes of wingless and wing morphs were assembled and annotated separately to identify potentially exclusively or differentially expressed transcripts between these two morphs, in which 3 126 and 3 392 unigenes annotated in Nr (Non-redundant protein sequence) database were found in wingless or wing morphs exclusively. Moreover, 3 187 up- and 1 880 down-regulated genes were identified in wing versus wingless aphid. Pathways analysis suggested the involvement of differentially expressed genes in multiple cellular signaling pathways involved in wing morphs determination, including lipid catabolic and metabolism, insulin, ecdysone and juvenile hormone biosynthesis. The expression levels of related genes were validated by the reverse transcription quantitative real time polymerase chain reaction (RT-qPCR) soon afterwards. Conclusions The present study identified the effects of postnatal crowding on wing morphs induction and demonstrated that the critical population density for wing morphs formation in A. gossypii was 20 nymphs·cm− 2. Comparative transcriptome analysis provides transcripts potentially expressed exclusively in wingless or wing morph, respectively. Differentially expressed genes between wingless and wing morphs were identified and several signaling pathways potentially involved in cotton aphid wing differentiation were obtained.